LEADERSHIP AND PUBLIC SERVICE: ANALYZING THE IMPACT OF VILLAGE HEADS IN RURAL GOVERNANCE - Saragih, Jopinus (KOMITMEN: Jurnal Ilmiah Manajemen, 2024)
This study examines the role of village head leadership in the delivery of public services in villages within the Siwalungun Regency, North Sumatra. Utilizing a qualitative approach and a case study design, the research explores the dynamic and multifaceted responsibilities of village heads, including their influence on public administration, healthcare, education, and infrastructure development. The findings reveal that effective leadership by village heads significantly enhances the quality of public services and increases community satisfaction. Village heads who demonstrate proactive and responsive leadership, act as facilitators and mediators, and initiate programs such as â€œHealthy Villageâ€ can address public needs efficiently. However, village heads face numerous challenges, including limited resources, both in terms of budget and human resources, as well as inadequate infrastructure. Social and political dynamics further complicate their leadership roles, often requiring them to mediate conflicting interests and navigate political pressures. Despite these challenges, village heads who adopt adaptive and innovative strategies, and collaborate effectively with various stakeholders, are more successful in overcoming these obstacles. This study underscores the crucial role of village head leadership in improving public service delivery and fostering community development. The study recommends capacity-building initiatives for village heads through training and mentoring, and the formulation of policies that support their leadership in enhancing public services and community welfare. The insights gained from this study contribute to better governance at the village level and highlight the importance of strong leadership for sustainable and equitable development.